A Review of Small Screen and Internet Technology–Induced Pathology as a Lifestyle Determinant of Health and Illness. Issue 2 (March 2020) - Stevens, John; Egger, Garry
Most advances in humanity have been related to the discovery or introduction of new innovations and/or technology. There should be no suggestion that all technology is pathological or that major advances in health, science, and well-being have not come from industrial and technological advances. However, just like the invention of the wheel would have no doubt caused people to be injured and modern lifesaving medicines can have side effects, modern technology can have a downside, which needs to be recognized. This article explores some of the pathologies linked to small screen and internet technologies (personal computers, communication devices, and the internet). The uptake and impact of this set of technologies is pivotal in redefining our lifestyle behaviors and environment: the way we work, shop, seek entertainment, communicate, socialize, reproduce, interact with the environment, and seek information.